2015
DOI: 10.3109/2000656x.2015.1053398
|View full text |Cite
|
Sign up to set email alerts
|

Gynecomastia: A systematic review

Abstract: Several different surgical methods have been described with good results, minimal scars, and various levels of complications. Traditional surgical excision of glandular tissue combined with liposuction provides most consistent results and a low rate of complications. Pubertal gynecomastia may safely be managed by pharmacological anti-oestrogen treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 27 publications
1
43
0
4
Order By: Relevance
“…UAL usually eliminates the problem of excessive skin by means of skin contraction. Nevertheless, this technique should be performed with special care to avoid the risk of thermal burns (1,8 (8,9). Proponents of these techniques have reported a better excision of fibrous fat with contour control, and postoperative skin contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UAL usually eliminates the problem of excessive skin by means of skin contraction. Nevertheless, this technique should be performed with special care to avoid the risk of thermal burns (1,8 (8,9). Proponents of these techniques have reported a better excision of fibrous fat with contour control, and postoperative skin contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Fugerland et al (8), in a systematic review of the relevant literature, indicated that although the majority of surgical techniques used to correct gynecomastia are associated with favorable outcomes, minimal scars, and various complications, the most consistent results have been achieved by a combination of liposuction and tradional surgical excision. Kim et al (13) reported that the patients who were operated with a combination of liposuction +subcutaneous mastectomy had better outcomes than those who underwent liposuction alone.…”
Section: Discussionmentioning
confidence: 99%
“…Excess skin is the limiting factor for this technique. Due to the weak data, no recommendation can be made with regard to the best surgical approach [30]. …”
Section: Conservative and Surgical Managementmentioning
confidence: 99%
“…Gynecomastia is described as the enlargement of male breast tissue [1]. It is a common condition that can be determined at various levels in 40-55% of males [2,3]. In addition to being able to occur due to the benign proliferation of the breast glandular tissue, gynecomastia can occur due to the increased adipose tissue amount on the pectoral muscle, and this latter condition is called pseudogynecomastia.…”
Section: Introductionmentioning
confidence: 99%
“…Although gynecomastia is mostly bilateral, it can be observed to be unilateral or asymmetrical [3]. Simon's classification is mostly used in clinical classification.…”
Section: Introductionmentioning
confidence: 99%